Prevalencia de Brucella Canis y factores asociados en Caninos Domésticos (canis familiaris) del Barrio Cuilche Miño de la Parroquia de San Juan de Pastocalle. - Sigcha Saracay, Tania Yomira (2018)
The present investigation was conducted in the Cuilche Miño neighborhood of the parish of San Juan de Pastocalle, "the Brucella canis is a zoonotic disease, the frequency of occurrence is given by severe outbreaks of canine abortions, becoming an important focus is a means of contagion to people, this study was also done by the lack of information on this disease, establishing as objective, determine the prevalence of Brucella Canis in domestic canines (Canis familiaris) of the aforementioned locations, To calculate the prevalence of Brucella canis in domestic canines, we proceeded to the collection of bibliographic information to obtain technical knowledge about the disease, later we extracted information from the owners and dogs, to proceed to translate into the respective surveys and clinical histories, with in order to collect data, from which blood samples were taken , to detect the presence of antigens, by means of the Rapid, Test Kit Ab using the diluent buffer, to establish the presence of Brucella canis in the blood samples obtained from the canines of the Cuilche Miño neighborhood, the investigation was based on 75 Canis familiaris, where the sampled group consisted of 26 females which represents 35% and 65% of the canines sampled are 49 males, where of the 75 Canis familiaris 19% had a house, 99% are in contact with other animals , 85% of canines are fed twice a day and 39% of canines have veterinary attention. The results obtained with the Ab Brucella canis kit test were, 1 positive canine and 74 of the canis were negative. represents 99%, the canine found positive with the kit was again submitted to study, through a Livex laboratory which ruled out that it was positive to Brucella canis, therefore it was established that the of Brucella canis in Canis familiaris, has no relationship with; age, sex, reproduction and feeding, resulting in 0% prevalence of Brucella canis in domestic canines of the Cuilche Miño neighborhood of the canton of Latacunga, which provides the residents of the studied district with information about Brucella canis and the current prevalence that exists in the canines of the sector, where the residents are made aware so that they take the appropriate care with their canines.